1966
DOI: 10.1002/cne.901280110
|View full text |Cite
|
Sign up to set email alerts
|

Increases in cortical depth and glia numbers in rats subjected to enriched environment

Abstract: We have previously reported anatomical and chemical changes in the cerebral cortex of rats living in an enriched, stimulating environment. The present study includes additional histological measures such as more extensive depth measures, differential cell counts, and cell size measurements.Celloidin-embedded, thionin-stained sections of the visual cortex from environmentally enriched rats and their impoverished littermates were measured. Two methods for calculating cortical depths were used: one, with an ocula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
135
2
6

Year Published

1972
1972
2022
2022

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 384 publications
(155 citation statements)
references
References 11 publications
11
135
2
6
Order By: Relevance
“…::z: A number of investigators have reported that giving a group of rodents prolonged informal experience in an enriched environment produces significant changes in chemical and anatomical brain measures (e.g., Altman & Das, 1964;Bennett, Diamond, Krech, & Rosenzweig, 1964;Brown & King, 1971; Diamond, Law, Rhodes, Lindner, Rosenzweig, Krech, & Bennett, 1966;Henderson, 1970;Krech, Rosenzweig, & Bennett, 1960;La Torre, 1968;Mpllgaard, Diamond, Bennett, Rosenzweig, & Lindner, 1971;Rosenzweig & Bennett, 1969;Rosenzweig, Bennett, & Diamond, 1972a;Rosenzweig, Krech, Bennett, & Diamond, 1962;Walsh, Budtz-Olsen, Penny, & Cummins, 1969). Until now, the respective roles of the social grouping and of the enriched inanimate environment have not been determined, and doing so is the purpose of this study.…”
Section: Lbl-01511mentioning
confidence: 99%
“…::z: A number of investigators have reported that giving a group of rodents prolonged informal experience in an enriched environment produces significant changes in chemical and anatomical brain measures (e.g., Altman & Das, 1964;Bennett, Diamond, Krech, & Rosenzweig, 1964;Brown & King, 1971; Diamond, Law, Rhodes, Lindner, Rosenzweig, Krech, & Bennett, 1966;Henderson, 1970;Krech, Rosenzweig, & Bennett, 1960;La Torre, 1968;Mpllgaard, Diamond, Bennett, Rosenzweig, & Lindner, 1971;Rosenzweig & Bennett, 1969;Rosenzweig, Bennett, & Diamond, 1972a;Rosenzweig, Krech, Bennett, & Diamond, 1962;Walsh, Budtz-Olsen, Penny, & Cummins, 1969). Until now, the respective roles of the social grouping and of the enriched inanimate environment have not been determined, and doing so is the purpose of this study.…”
Section: Lbl-01511mentioning
confidence: 99%
“…Because the differences were largest in the visual cortex, much of the subsequent work was aimed at determining the underlying morphology that contributes to the gross difference in size in this region (e.g. Diamond et al, 1964;Diamond et al, 1966;Volkmar and Greenough, 1972). Although not a ubiquitous phenomenon, morphological plasticity following exposure to EC has been demonstrated in several other brain regions that are involved in the processing and/or response to environmental stimuli, including the auditory cortex (Greenough et al, 1973), primary somatosensory cortex (Coq and Xerri, 1998), hippocampus and entorhinal cortex (Fiala et al, 1978;Moser et al, 1997;Rampon et al, 2000), amygdala (Nikolaev et al, 2002), basal ganglia (Comery et al, 1995;Comery et al, 1996) and cerebellar cortex .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, exposure to an EE has been shown to induce biochemical and structural changes in several brain regions in particular in the cortex and the hippocampus (Diamond et al, 1976;Kempermann et al, 1997;Nithianantharajah and Hannan, 2006;van Praag et al, 2000). Alterations include increased brain weight and size , increased neurotransmitter levels such as acetylcholine , serotonin and noradrenaline (Chaouloff, 1989), as well as enhanced gliogenesis (Diamond et al, 1966) and neurogenesis (Kempermann et al, 1997). These alterations may be due, at least in part, to changes in gene expression produced by environmental stimulation.…”
Section: Introductionmentioning
confidence: 99%